2019
DOI: 10.1177/0022243719881618
|View full text |Cite
|
Sign up to set email alerts
|

A Multiattribute Benefits-Based Choice Model with Multiple Mediators: New Insights for Positioning

Abstract: Previous research has demonstrated that consumers evaluate products according to their perceived benefits when making a choice. This article extends prior work by proposing a method that evaluates the degree to which multiple a priori defined benefits mediate product choices. The model is the first to consider process heterogeneity—that is, heterogeneity in how consumers perceive multiple attributes to positively or negatively affect multiple benefits simultaneously and the contribution of each benefit to prod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 92 publications
(169 reference statements)
0
4
0
Order By: Relevance
“…Here, less than one-quarter of participants reported looking for whole grain foods specifically and almost half never looked for the term ‘whole grains’ on packaging. In research focused on multi-attribute choice modelling using bread as the example, Burke et al [ 38 ] found that whole grain was rated highly for both healthful and value for money by consumers. If more manufacturers routinely declared the percentage of whole grain content on packs, there would be a wider range of whole grain products for consumers to easily identify, providing the greatest opportunity to improve consumption patterns of whole grain foods across the population.…”
Section: Discussionmentioning
confidence: 99%
“…Here, less than one-quarter of participants reported looking for whole grain foods specifically and almost half never looked for the term ‘whole grains’ on packaging. In research focused on multi-attribute choice modelling using bread as the example, Burke et al [ 38 ] found that whole grain was rated highly for both healthful and value for money by consumers. If more manufacturers routinely declared the percentage of whole grain content on packs, there would be a wider range of whole grain products for consumers to easily identify, providing the greatest opportunity to improve consumption patterns of whole grain foods across the population.…”
Section: Discussionmentioning
confidence: 99%
“…Private labels Consumers tend to have intuitions regarding the healthiness of private label products, as they judge private label products as unhealthier than their national brand counterparts. The presence of a private label brand on a product has been found to have a negative impact on the perceived health benefits of the product (Burke et al, 2020;Consumer Reports, 2010). However, objectively, this is not always true (Consumer Reports, 2010).…”
Section: Prior Research On Health Symbolsmentioning
confidence: 99%
“…Several methods and models have been developed to account for differences in individual preferences (e.g. Burke et al, 2020), but also individual differences in choice variability (e.g. Burke & Reitzig, 2007;Fiebig et al, 2010; Islam et al, 2007;Magidson & Vermunt, 2007;Swait & Louviere, 1993).…”
Section: Discussionmentioning
confidence: 99%